The effect of an informative 360-degree virtual reality video on anxiety for women visiting the one-stop clinic for abnormal uterine bleeding: A randomized controlled trial (VISION-trial). (May 2022) - Reinders, Imke M.A.; Cremers, Gaston R.; van Rooijen, Stefanus J.; Leemans, Jaklien C.; Perquin, Christel W.; Geomini, Peggy M.A.J.; Maas, Jacques W.M.; Bongers, Marlies Y.
Highlights: Watching an informative 360-degree VR-video does not reduce preprocedural anxiety. A third of the included women did not watch the allocated VR-video. In general, these reluctant women were more anxious at baseline. Of the women who watched the video, the majority found that it was of added value. Future research should focus on identifying anxious women and exploring strategies for them. Abstract: Objective: To evaluate the effect of an informative 360-degree virtual reality (VR) video on preoperative anxiety before visiting a one-stop clinic for abnormal uterine bleeding. Study Design: A randomized controlled trial was performed in a teaching hospital in the Netherlands. A total of 83 women scheduled for a first consultation at the one-stop clinic between April 2017 and September 2017 were included in the analysis. All women received a standard information leaflet about the clinic. 40 women were randomized to receive a 360-degree VR-video of the clinic in addition. The primary outcome was change in the Visual Analogue Scale for Anxiety (VAS-A), measured at baseline (before randomization) and in the waiting room (before visit, after randomization). Anxiety assessed with the State-Trait Anxiety Inventory (STAI-S) was a secondary outcome. Other secondary outcomes included anxiety during the visit and the opinion of the women about the provided information. Results: Only 27 out of the 40 women actually watched the VR-video. Women in the VR-group who actually watched the video reported lower levels of anxiety at baseline compared to women in the VR-group who did not watch the video. In the intention-to-treat analysis, there was no difference in change in anxiety between the VR-group and the control group (mean difference VAS-A = 0.07, 95% CI –0.96 to 1.10; mean difference STAI-S = 1.97, 95% CI –1.82 to 5.77). In the per-protocol analysis, women in the VR-group reported lower anxiety scores in the waiting room. However, the change in anxiety scores between baseline and waiting room was comparable in both groups. 31% of the women who watched the VR-video reported that the video resulted in a reduction of anxiety, 69% reported that the video is of added value and 65% would use a VR-video again in future. Conclusions: Adding the informative 360-degree VR-video to conventional information did not result in a reduction of anxiety prior to visiting the one-stop clinic. However, the majority of women who watched the video felt that it was of added value. Remarkable was that women who reported higher anxiety at baseline seemed less willing to watch the video.